Isolation and characterization of Stenotrophomonas pavanii GXUN74707 with efficient flocculation performance and application in wastewater treatment - Qin, Siqi; Li, Qiao; Dou, Jin; Man, Yuanyuan; Wu, Liuyan; Tian, Hongmei; Jiang, Mingguo; Liu, Guofang (Frontiers in Microbiology, 2024)
The identification of microorganisms with excellent flocculants-producing capability and optimization of the fermentation process are necessary for the wide-scale application of bioflocculants. Therefore, we isolated and identified a highly efficient flocculation performance strain of Stenotrophomonas pavanii GXUN74707 from the sludge. The optimal fermentation and flocculation conditions of strain S. pavanii GXUN74707 was in fermentation medium with glucose and urea as the carbon and nitrogen sources, respectively, at pH 7.0 for 36 h, which treatment of kaolin suspension with 0.5 mL of the fermentation broth resulted in a flocculation rate of 99.0%. The bioflocculant synthesized by strain S. pavanii GXUN74707 was found mainly in the supernatant of the fermentation broth. Chemical analysis revealed that the pure bioflocculant consisted of 79.70% carbohydrates and 14.38% proteins. The monosaccharide components of MBF-GXUN74707 are mainly mannose (5.96 µg/mg), galactose (1.86 µg/mg), and glucose (1.73 µg/mg) . Infrared spectrometric analysis showed the presence of carboxyl (COO-), hydroxyl (-OH) groups.The SEM images showed clumps of rod-shaped bacteria with adhesion of extracellular products. Furthermore, the strain decolored dye wastewater containing direct black, direct blue, and Congo red by 89.2%, 95.1%, and 94.1%, respectively. The chemical oxygen demand (COD) and biological oxygen demand (BOD) removal rates after treatment of aquaculture wastewater with the fermentation broth were 68% and 22%, respectively. This study is the first to report the performance and application of strain Stenotrophomonas pavanii in wastewater flocculation. The results indicate that strain S. pavanii is a good candidate for the production novel bioflocculants and demonstrates its potential industrial practicality in biotechnology processes.